ARTIFICIAL INTELLIGENCE APPLICATIONS AND IMPACT ON CONSUMERS – WITH A VIEW ON ROMANIAN CONSUMERS’ PERCEPTIONS AND ATTITUDES RELATED TO AI - Emanuel SANDA (Studia Universitatis Babeş-Bolyai Negotia, 2021)
Artificial Intelligence based technologies are becoming more and more pervasive in people’s lives. Whether it takes the form of machine learning algorithms, Internet of Things smart devices, virtual assistants, chatbots, robots, AR/VR experiences, consumers are faced directly or indirectly, conscientiously or unconscientiously, with a variety of incarnations of what is generically called AI. The current debate surrounding AI seems to focus on a few major aspects related to this next technological breakthrough. Right from the start, there is intense discussion even around the definition of AI: what is and what is not AI, how broad of a definition can be applied, and which of the many current and envisaged applications are actually ‘intelligent’. Then, there is the critical issue of the use of consumers’ personal data and underlying privacy issues, as AI seems to be built and thrive on being fed enormous amounts of data of various kinds. And lastly, there seems to be increasing concern regarding the potential for AI to evolve into AGI (Artificial General Intelligence – independent self-reliant robots) and the threats this poses to humanity. A subject of potentially equal importance could be AI applications and implementations are impacting individuals’ lives and the manner in which people relate to, perceive and assess AI and the underlying current technologies, both in terms of the impact in their daily lives, as well as in terms of expected prospects for the future. This paper looks at the progress made so far in addressing some of the above questions and, by analyzing data from EU’s 2017 Eurobarometer study, attempts to reveal how various Romanian consumer segments perceive and relate to AI and current technologies. It identifies potential emerging inequalities from access, acceptance and usage of these technologies at present and in the future. The paper also sets out future directions for further understanding of the intricate relationship between human consumers and emerging AI tech, both in terms of benefits as well as potential threats. JEL Classification: M30, M31, M39